Analisa Debit Banjir Rencana di Ruas Jalan Simpang Seputuk Kecamatan Muruk Rian Kabupaten Tana Tidung Provinsi Kalimantan Utara dengan Metode HSS Snyder dan HSS Nakayasu - Isak Bella Mata; Suhudi Suhudi; Erizaldy Azwar (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2025)
The Seputuk and Rian Watersheds in Muruk Rian Subdistrict, Tana Tidung Regency, North Kalimantan Province, are areas that are prone to flooding due to high rainfall and the morphological conditions of the watersheds. This study aims to analyze and compare the planned flood discharge on the Simpang Seputuk Road section using the Snyder Synthetic Unit Hydrograph (HSS) and Nakayasu HSS methods. The data used is the maximum daily rainfall from the Salap Rainfall Station during the 2008–2021 period. The planned rainfall analysis was carried out using the Gumbel and Log Pearson Type III probability distributions, followed by a suitability test using the Chi-Square and Smirnov Kolmogorov methods. The selected planned rainfall was transformed into effective rainfall as input in the flood discharge calculation. The analysis results show that the Nakayasu HSS method produces a higher peak discharge than the Snyder HSS method in both watersheds. In the Seputuk watershed, the Nakayasu method's peak discharge for a 25-year return period reached 501.80 m³/sec, while the Snyder method produced 233.47 m³/sec. Meanwhile, in the Rian watershed, the Nakayasu method produced a peak discharge of 319.83 m³/sec and the Snyder method produced 73.06 m³/sec. This difference shows that the Nakayasu HSS method is more conservative and sensitive to watershed morphometric characteristics, making it more suitable for flood control planning in areas with flood risk. Meanwhile, in the Rian watershed, the Nakayasu method produced a peak discharge of 319.83 m³/sec and the Snyder method produced 73.06 m³/sec. This difference indicates that the Nakayasu HSS method is more conservative and sensitive to the morphometric characteristics of the watershed, making it more suitable for flood control planning in areas with high flood risk, while the Snyder method can be used as a preliminary estimate in watersheds with limited data.